Study of the causes of non-acceptance of VBAC in patients with previous one LSCS in a tertiary institution - Karmali, Deepa B.; Pednekar, Guruprasad; Nagarsenkar, Ajit A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Many women who are eligible candidates for a VBAC (Vaginal Birth after Caesarean) in the current pregnancy opt for a repeat LSCS (Lower Segment Caesarean Section) as a mode of delivery. We decided to evaluate the proportion of patients who opt out of a VBAC and to study the causality of this trend. Methods: All patients who presented to the Dept. of OBG in our institution and were eligible to have a VBAC were included in the study till the sample size of 100 cases was met. Consultant opinion was sought prior to deciding the mode of delivery. Results: Incidence of patients of previous one LSCS who were not willing for VBAC was 4%, out of total number of deliveries and 30.7%, out of all cases of patients with previous one LSCS. The reason for not opting for a VBAC in the current pregnancy in the majority of the eligible patients was the desire for a concurrent sterilization procedure. Others cited apprehension of a scar rupture or fear of labor pain or both as their primary reason for opting out of a VBAC. Conclusions: The high incidence of ERC (Elective Repeat Caesarean) as compared to TOLAC (Trial of Labour after Caesarean) has long-term clinical and financial implications. Counseling given to the pregnant woman with an emphasis on the advantages of VBAC in order that she opts for a VBAC with confidence and enthusiasm is the only way forward.